Menafsir Pemikiran John Locke tentang Demokrasi dan Implikasinya bagi Demokrasi dan Bonus Demografi di Indonesia - Rolin Ferdilianto Sandelgus Taneo (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2026)
This paper is a contextual interpretation of John Locke's thoughts on political philosophy (democracy), which holds that a democratic climate will function well if it includes attention to human rights, upholding the freedom of every person, and the right to own property. These three elements represent concrete manifestations of a good democratic climate. The author will then use this perspective to interpret the constellation of democracy in Indonesia, with its various ongoing struggles. A good democratic climate will, in fact, support the prospects of Indonesia's demographic bonus. If not addressed, the democratic system, with its various problems, could pose a challenge in responding to the demographic bonus, especially the Dream of a Golden Indonesia 2045. Using a literature study method, we will examine Locke's political philosophy, the issues of democracy, and the demographic bonus in Indonesia. It is hoped that this study will make a valuable contribution to improving the quality of Indonesian democracy and how to address the demographic bonus.